2020
DOI: 10.1097/01.aoa.0000661352.00928.f0
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Self-reported Prenatal Cannabis Use and Maternal, Perinatal, and Neonatal Outcomes

Abstract: (JAMA. 2019;322:145–152) The rate of cannabis use among pregnant women in Canada was 2% in 2017. With recent legalization, it is anticipated that cannabis use among pregnant women will continue to rise. Cannabinoids can cross the placenta and enter the fetal blood supply. Previous studies have demonstrated a relationship between pregnant mothers who use cannabinoids and increased incidence of low birth weight, small for gestational age (SGA), stillbirth, and admission to neonatal intensive care. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 0 publications
5
66
0
Order By: Relevance
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
“…37 In a recent registry-based study, cannabis use was associated with preterm birth and small-for-gestational-age birth. 38 Pregnant women 39 and couples 40 often prefer nonpharmacologic measures, such as CBT-I, over medications or even acupuncture. A recently published randomized controlled trial showed that pregnant women randomized to undergo CBT-I experienced a significantly greater reduction in insomnia severity and faster remission of insomnia compared with women assigned to a control intervention.…”
Section: Treatment Considerations For Insomnia In Pregnancymentioning
confidence: 99%
“…14 Despite the increasing prevalence of prenatal cannabis exposure, there have been relatively few investigations of its association with child outcomes. These studies have found evidence linking prenatal marijuana exposure to reduced birth weight 15 and cognition 16,17 as well as heightened risk for premature birth, 18 psychopathology (i.e., psychosis, internalizing, externalizing) [19][20][21] and sleep problems 22 among children. However, there has been limited crossstudy replication, e.g., [23][24][25] and studies have typically been unable to account for other potential confounding factors (e.g., maternal education, prenatal vitamin usage, child substance use, familial risk), leaving it possible that associations between prenatal marijuana exposure and negative outcomes among children may not be independent of them.…”
Section: Introductionmentioning
confidence: 99%